Sex Differences in Cardiac Mitochondria in the New Zealand Obese Mouse - John, Cathleen; Grune, Jana; Ott, Christiane; Nowotny, Kerstin; Deubel, Stefanie; Kühne, Arne; Schubert, Carola; Kintscher, Ulrich; Regitz-Zagrosek, Vera; Grune, Tilman (Frontiers in Endocrinology, 2018)
Background: Obesity is a risk factor for diseases including type 2 diabetes mellitus (T2DM) and cardiovascular disorders. Diabetes itself contributes to cardiac damage. Thus, studying cardiovascular events and establishing therapeutic intervention in the period of type T2DM onset and manifestation are of highest importance. Mitochondrial dysfunction is one of the pathophysiological mechanisms leading to impaired cardiac function. Methods: An adequate animal model for studying pathophysiology of T2DM is the New Zealand Obese (NZO) mouse. These mice were maintained on a high-fat diet (HFD) without carbohydrates for 13 weeks followed by 4 week HFD with carbohydrates. NZO mice developed severe obesity and only male mice developed manifest T2DM. We determined cardiac phenotypes and mitochondrial function as well as cardiomyocyte signaling in this model. Results: The development of an obese phenotype and T2DM in male mice was accompanied by an impaired systolic function as judged by echocardiography and MyH6/7 expression. Moreover, the mitochondrial function only in male NZO hearts was significantly reduced and ERK1/2 and AMPK protein levels were altered. Conclusions: This is the first report demonstrating that the cardiac phenotype in male diabetic NZO mice is associated with impaired cardiac energy function and signaling events.